PEMANFAATAN BUAH NIPAH DAN UMBI BIT PADA PEMBUATAN FRUIT LEATHER - Kamelia Sari; Usman Pato (Universitas Riau, 2022)
Fruit leather is a type of snack food made from fruit in the form of a thin sheet. It has a consistent, distinctive taste depending on the fruit used. This study aimed to obtain the best ratio between Nipah pulp and beetroot pulp to make fruit leather. This study used a completely randomized design (CRD) consisting of four treatments and four replications. The treatment in this study was the comparison of Nipah fruit pulp and beetroot pulp, namely NB1 (85:15), NB2 (75:25), NB3 (65:35), and NB4 (55:45). The parameters observed in this study were water, ash, pH, fiber, antioxidant activity, and sensory tests for color, taste, texture, and overall assessment. Data were statistically analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% level. The results showed that the ratio of Nipah fruit pulp and beetroot pulp significantly affected water content, ash content, ph content, crude fiber content, antioxidant activity, sensory tests on color, taste, aroma, and texture, and overall assessment. The best treatment of fruit leather in this study was Nipah fruit pulp and beetroot pulp (85:15), with moisture content 7.63%, ash 0.78%, pH 4.40, crude fiber 2.62%, antioxidant activity 118.31 ppm, red color (score 2.00), sweet taste (score 2.00), the aroma was slightly fragrant with Nipah fruit and beetroot (score 3.00), chewy texture (score 4.43) and the overall rating is favored by the panelists (score 4.43).